Role of transcranial colour-coded duplex sonography in stroke management (2015)
The development of transcranial colour-coded duplex sonography (TCCS) has resurrected the hope of safe, real time bedside brain imaging beyound childhood. This review article provides an overview of the role of TCCS in the management of patients with stroke. The objective is to stimulate interest in the field of neurosomology as a potential means of improving neurological outcome for stroke patients and a area for stroke research endeavours in Africa. Literature search was done on MEDLINE, Cochrane library, and GoogleScholar database with the following keywords: transcranial colour Doppler, Transcranial duplex sonography,stroke, infarct and haemorrhage. We also identified relevant articles from the references section of studies produced by our literature search. We discussed the roles of TCCS to discriminate ischaemic from haemorrhagic forms; unravel the mechanism of stroke; monitor temporal evolution of stroke and predictors of stroke outcome; and promote better understanding of the epidemiology of stroke. It emerging role as a potent point-of-care imaginf modality for definitive treatment in ischaenic stroke within and outside the hospital setting is also highlighted. Comparison of TCCS with alternative modalities for neuroimaging for stroke patients in Africa is presented vis-a-vis the potential economic relief which widespread adoptionof TCCS may provide. We advocate capacity building for TCCS and suggest some action plans required to achieve safe, cheap, affordable and reliable ultrasound based neuroimaging for stroke patients in resource limited areas of Africa.